Sensorless Control of a Fault Tolerant PMSM Drives in Case of Single-phase Open Circuit Fault - Kamel Saleh; Mark Sumner (Institute of Advanced Engineering and Science, 2016)
This paper introduces a sensorless-speed-controlled PMSM motor fed by a four-leg inverter in case of a single phase open circuit fault regardless in which phase is the fault. To minimize the system performance degradation due to a single phase open circuit fault, a fault tolerant control strategy that includes taking appropriate actions to control the two remaining healthy currents is used in addition to use the fourth leg of the inverter. Tracking the saliency is done through measuring the dynamic current responses of the healthy phases of the PMSM motor due the IGBT switching actions using the fundamental PWM method without introducing any modification to the operation of the fourth leg of the inverter. Simulation results are provided to verify the effectiveness of the proposed strategy for sensorless controlling of a PMSM motor driven by a fault-tolerant four-phase inverter over a wide speed ranges under the case of a single phase open circuit.